Research of childhood tuberculosis in suspected populations by molecular methods: A multicenter study in China - Li, Chunling; Wang, Shifu; Yu, Hui; Wang, Jiangxia; Deng, Jikui; Wang, Hongmei; Hua, Chunzhen; Zhuo, Zhiqiang; Chen, Lei; Hao, Jianhua; Gao, Wei; Zhang, Hong; et al. (Frontiers in cellular and infection microbiology, 2022)
The research of childhood tuberculosis is inadequate in china. The cross-priming amplification (CPA) of specific DNA in clinical samples is increasingly adopted for the diagnosis of childhood tuberculosis. In this study, a multicenter research was performed to investigate the incidence and characteristics of childhood tuberculosis in suspected populations mainly by CPA method. 851 children suspected of tuberculosis were enrolled in seven centers across China. All samples were tested by a CPA method and 159 subjects were tested by Xpert MTB/RIF and liquid culture method in parallel to assess the reliability of the CPA method. A positive result in any one of the three methods provided a definitive diagnosis of Mycobacterium tuberculosis complex (MTBC) infection. The MTBC-positive rate was 9.5% (81/851) by the combined methods; 93.8% of the cases were detected by CPA technology (76/81). The rate of pulmonary infection was significantly higher than that of extrapulmonary infection (7.1%, 60/851 vs 2.5%, 21/851; P < 0.001). Scrofula was the predominant type of extrapulmonary tuberculosis. The MTBC positive rates in 12-18-year-old group (middle school), was 28.4% (23/81), higher than in those under-six-year-old (preschool; 39/525) and the 6~11-year-old (primary school; 18/235) groups combined (P < 0.001). The MTBC positive rate in patients with a clear history of tuberculosis exposure was significantly higher than in cases in which there was no history of tuberculosis contact(35.3%, 18/51 vs 7.8%, 61/782; P < 0.001). In conclusion, this multicenter investigation showed that pulmonary tuberculosis and extrapulmonary tuberculosis are not uncommon in children in China, with teenagers being particularly susceptible to infection. The incidence of pulmonary tuberculosis in children is higher than that of extrapulmonary tuberculosis. History of exposure to tuberculosis is a high risk factor for childhood tuberculosis.